2009
DOI: 10.1038/hdy.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for relatedness in Bayesian models for genomic data association analysis

Abstract: For small pedigrees, the issue of correcting for known or estimated relatedness structure in population-based Bayesian multilocus association analysis is considered. Two such relatedness corrections: [1] a random term arising from the infinite polygenic model and [2] a fixed covariate following the class D model of Bonney, are compared with the case of no correction using both simulated and real marker and geneexpression data from lymphoblastoid cell lines from four CEPH families. This comparison is performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 87 publications
4
37
0
Order By: Relevance
“…Although many authors have found the impact of the polygene insignificant (e.g., Calus and Veerkamp 2007;Pikkuhookana and Sillanpää 2009), some are convinced of its importance (e.g., de los Lund et al 2009). In our example analyses the estimates of the polygenic component are negligible and have no influence on the estimated breeding value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many authors have found the impact of the polygene insignificant (e.g., Calus and Veerkamp 2007;Pikkuhookana and Sillanpää 2009), some are convinced of its importance (e.g., de los Lund et al 2009). In our example analyses the estimates of the polygenic component are negligible and have no influence on the estimated breeding value.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its weaker shrinking ability the Student's t prior is more prone to the problem than the Laplace prior. In fact, Pikkuhookana andHayashi andIwata (2010) have noted that adding a point mass at zero to a Student's t prior model improves the performance, due to the elimination of the cumulative effect of a multitude of insignificant but nonzero marker effects. Although the Laplace prior generates more sparseness, there is evidence in support of the usefulness of the Laplace and point mass mixture prior (Shepherd et al 2010).…”
mentioning
confidence: 99%
“…Setakis et al (2006) suggested the use of a much larger number of null markers as regression covariates to eliminate most of the variation due to population structure. In addition, multilocus models have been shown to possess the potential to account for population stratification, potentially as the variable selection process selects also those markers that explain a part of the confounding variation (Iwata et al, 2007;Pikkuhookana and Sillanpää, 2009;Kärkkäinen and Sillanpää, 2012). Another benefit of simultaneously taking multiple QTL into account in the model is that the QTL detection power may also be enhanced (Iwata et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As in Pikkuhookana and Sillanpää, (2009), there is another source of sparseness in our model, given by the indicator variables. In principle, the degree of sparseness can be controlled by specifying a small prior probability to include each marker into the model.…”
Section: Model Selectionmentioning
confidence: 99%
“…Although these indicators provide a natural way to monitor posterior occupancy of QTLs, the real reason for having them in the model is to improve heritability estimation as shown by Pikkuhookana and Sillanpää (2009). For details, see the subsection dealing with Heritabilities and genetic covariances/correlations.…”
Section: Multiple Trait Qtl Modelmentioning
confidence: 99%